PERAN PENDIDIKAN PKN TERHADAP KARAKTER KEBANGSAAN PESERTA DIDIK DI MTS MIFTAHUL MUNIR DESA KAJUANAK KECAMATAN GALIS KABUPATEN BANGKALAN - Wahdana; Dian Eka Indriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the role of civic education on the national character of students at Mts Miftahul Munir Kajuanak. This study uses a descriptive qualitative method. The data collection techniques used are observation, interviews, and documentation. The results of this study indicate that 1. Civic Education (PKn) at MTs Miftahul Munir has a significant role in forming an attitude of tolerance among students. With a learning approach that highlights the values of diversity, students are taught to appreciate differences in ethnicity, culture, and social background. Based on the results of the interview, it was seen that students were increasingly able to communicate well and respect each other, thus creating a harmonious atmosphere. 2. PKn was also successful in fostering love for the homeland among students. Student participation in various national activities, such as flag ceremonies and commemoration of national santri day, reflects that they absorb national values. Pride in Indonesian identity and the spirit of nationalism grow through real experiences and relevant learning.